Organizational Commitment in View of Job Satisfaction in Production Employees at PT.X - Ramadan, Salma Fairus; Mora, Linda; Tyas, Devi Marganing (International Journal of Economics and Management Research, 2024)
An organization is a system consisting of individuals who influence each other and work together to achieve certain goals. Organizational goals can be achieved if human resource management is done well, which in turn will increase organizational commitment and generate job satisfaction. This study aims to determine the effect of job satisfaction on organizational commitment in production employees at PT.X. This research method uses quantitative research methods with the research design used is associative causality. The population in this study consisted of 121 production employees in the Aluminum department. The sampling technique used was non-probability sampling with the total sampling method, so that the entire population consisting of 121 production employees was sampled in this study. The scale used to measure job satisfaction is the Job Satisfaction Survey (JSS). While the scale used to measure organizational commitment is the Organizational Commitment Questionnaire (OCQ). Data analysis techniques in this study include classical assumption tests, (normality test, and linearity test), simple linear regression analysis, and the coefficient of determination. The results showed that there is an effect of job satisfaction on organizational commitment in production employees at PT X. Job satisfaction contributes 64.5% to organizational commitment and 35.5% is influenced by other factors